2013
DOI: 10.1016/j.jpedsurg.2012.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Short-term intravenous fish oil and pediatric intestinal failure associated liver disease: 3-year follow-up on liver function and nutrition

Abstract: Intravenous fish oil (FO) has changed the management of intestinal failure associated liver disease (IFALD). This report describes two IFALD patients who received FO for 5 and 10 months, respectively and reports on their 3-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Our results lend further support to case reports and recent studies regarding FO's efficacy and safety as a therapy for IFALD 9 13 , 16 20 . Puder et al 10 and Premkumar et al 11 published the results of the largest cohorts to date.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results lend further support to case reports and recent studies regarding FO's efficacy and safety as a therapy for IFALD 9 13 , 16 20 . Puder et al 10 and Premkumar et al 11 published the results of the largest cohorts to date.…”
Section: Discussionsupporting
confidence: 88%
“…A FO treatment course of 24 weeks was selected based on available evidence from studies at the design of this study, our experience with FO under compassionate use, and to minimize FO cost and potential adverse events 9 , 12 , 20 , 21 . Considering the number of children who would satisfy the study's inclusion criteria and that some patients may require PN for years, the cost of prolonged FO treatment would have been prohibitive.…”
Section: Introductionmentioning
confidence: 99%
“…During this time, other children remained cholestasis‐free and/or achieved enteral autonomy. Based on our findings and the results of other studies, we believe that extending FO beyond 6 months could help prevent cholestasis redevelopment and liver failure in some children with IF …”
Section: Discussionsupporting
confidence: 74%
“…None of these subjects succumbed to liver failure or required a transplant . Based on our data and published literature, we amended our compassionate‐use protocol so that children who remain PN‐dependent could continue FO indefinitely …”
Section: Discussionmentioning
confidence: 99%
“…The emulsifier in this lipid emulsion, based on glycerol and egg yolk phospholipid, is similar to that used in soybean IVFE. A number of case reports, case series, and retrospectively controlled trials of IV fish oil have been reported in infants with or at risk for IFALD 98 107 . No therapeutic or prophylactic double‐blind randomized controlled trials have been completed to demonstrate the efficacy of this therapy for this indication.…”
Section: Case Examplesmentioning
confidence: 99%